Identifikasi Penentuan Skala Prioritas Penanganan Genangan Atau Banjir Di Kecamatan Karawang Barat - Trisha Ajeng Larasaty; M. Candra Nugraha; Etih Hartati (Jurnal Serambi Engineering, 2020)
West Karawang District is a center of local activities with a service scope the whole Karawang Regional with most populous region by 142.509 persons. Based on Karawang Regional Spatial Plans Year 2011 – 2031, West Karawang Sub-district is a flooded vulnerable area when rain season. That area is along the Citarum River stream with. Priority scale determination of flood is done with comparison method of the existing flood condition with the parameters in Peraturan Menteri Pekerjaan Umum dan Perumahan Rakyat No.12 Tahun 2014 tentang Penyelenggaraan Sistem Drainase Perkotaan. There were 13 flood points in West Karawang District with the highest priority scale, Tanjungpura Sub-District. In Tanjungpura Sub-District, there are 3 flood points with a height of 50-30 cm, 1 Ha of flood area, and the length of flood lasts for 10 hours. The puddle is located in a densely populated residential area which causes a lot of losses to residents.